2011
DOI: 10.1152/ajplung.00328.2010
|View full text |Cite
|
Sign up to set email alerts
|

A role for zinc in regulating hypoxia-induced contractile events in pulmonary endothelium

Abstract: We previously reported that zinc thiolate signaling contributes to hypoxic contraction of small, nonmuscularized arteries of the lung. The present studies were designed to investigate mechanisms by which hypoxia-released zinc induces contraction in isolated pulmonary endothelial cells and to delineate the signaling pathways involved in zinc-mediated changes in the actin cytoskeleton. We used fluorescence-based imaging to show that hypoxia induced time-dependent increases in actin stress fibers that were revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…ZIP12 expression may increase PVR by increasing pulmonary vascular tone. Zinc-thiolate signaling has been reported to mediate the constriction of pulmonary microvascular endothelial cells in acute hypoxia through activation of protein kinase C and inhibition of myosin light chain phosphatase, inducing stress fibre formation and endothelial cell contraction 12 . We have shown that ZIP12 targeted siRNA attenuates stress fibre formation in human pulmonary vascular smooth muscle cells cultured in hypoxia (Extended Data Fig.…”
mentioning
confidence: 99%
“…ZIP12 expression may increase PVR by increasing pulmonary vascular tone. Zinc-thiolate signaling has been reported to mediate the constriction of pulmonary microvascular endothelial cells in acute hypoxia through activation of protein kinase C and inhibition of myosin light chain phosphatase, inducing stress fibre formation and endothelial cell contraction 12 . We have shown that ZIP12 targeted siRNA attenuates stress fibre formation in human pulmonary vascular smooth muscle cells cultured in hypoxia (Extended Data Fig.…”
mentioning
confidence: 99%
“…Although a mechanistic interaction between minerals and WB myopathy is lacking, our data suggest that WB might be associated with mineral overload/deficiency. It has been shown that hypoxia increases intracellular Zn levels (Bernal et al, 2008) and intracellular Zn overload has been reported to alter skeletal muscle contractility (Isaacson and Sandow, 1963; Bernal et al, 2011). Hypoxia was also found to increase basal Ca and Na concentrations, and reduce K and P levels (Weiss et al, 1989; Yadav et al, 2013; Shi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Islets' β-cells are close to the fenestrated endothelium ( Fig 5 ), building a functional unit that is lost in islet transplantation procedures [ 36 , 37 ]. In other organs, such as the lung, free Zn 2+ induces endothelial cell contraction [ 38 ], a process that is augmented by nitric oxide [ 39 , 40 ]. This mechanism might also operate in pancreatic islets in hypoxic conditions in a process dependent on the generation of high levels of nitric oxide [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%